Capital and Marx's epistemological revolution from Neue Marx-Lektüre to Political Marxism - Čakardić, Ankica (Array, 2021)
The paper discusses the thesis about Marx’s “epistemological revolution” by elaborating two issues that incorporate two entirely different contemporary Marxist traditions. To give this undertaking a more precise formulation, in its first part, the study examines the relationship between theory and history within the critique of political economy, proposed by Michael Heinrich under the tradition known as Neue Marx-Lektü re. It then turns to introducing the second part of the discussion related to the “commercialization model” of capitalist development, outlined by Robert Brenner and Ellen Meiksins Wood within the context of the so-called Political Marxism. A special emphasis is thereby put on the latter, since it deals with the contemporary nature of a few distinct epistemological and methodological novelties of the Capital, as well as some posited in the Grundrisse.